The Influence of Preparation Methods on Phenolic Compounds Content in Green Tea Samples from the Libyan Market - Afaf Abozid,; Laila Benramadan,; Alshintari, Mohamed (AlQalam Journal of Medical and Applied Sciences, 2025)
Tea leaves are rich in polyphenols, including catechins and flavonoids, which exhibit potent antioxidant properties. These compounds play a critical role in combating oxidative stress, a key factor in the development of chronic diseases such as cancer, cardiovascular diseases, and neurodegenerative disorders. The extraction of these bioactive compounds from tea offers a sustainable source of antioxidants with significant health benefits. This study investigates the phenolic content of green tea samples available in the Libyan market, with a focus on the impact of traditional Libyan preparation methods. Using the Folin–Ciocalteu method, the phenolic profiles of seven green tea brands were quantified. The study also examines the effect of traditional Libyan preparation techniques, particularly the removal of the first tea boiling, on the concentration and efficacy of these compounds. Results reveal significant variability in phenolic content across different tea samples and preparation methods, emphasizing the importance of retaining the first boiled tea to preserve bioactive composition. This research provides valuable insights into optimizing tea preparation to maximize health benefits, offering practical guidance for consumers, and promoting the integration of traditional preparation methods into modern health practices.